2017
DOI: 10.1093/jac/dkx234
|View full text |Cite
|
Sign up to set email alerts
|

Structural modification of LPS in colistin-resistant, KPC-producing Klebsiella pneumoniae

Abstract: The pathway to colistin resistance in K. pneumoniae primarily involves lipid A modification with Ara4N in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 28 publications
5
55
0
Order By: Relevance
“…102 Interestingly, in both K. pneumoniae and A. baumannii, genomic sequencing studies have found mutations in a common regulatory pathway controlling LPS modification systems, indicating that LPS modification is key to resistance in both species. [103][104][105] This genomederived hypothesis that altered LPS modification underlies resistance was ultimately confirmed for both organisms by comparing LPS modifications in susceptible and resistant isolates. 103,106 An important caveat in studying resistance evolution in individual patients is that the larger epidemiological significance of observed resistance mutations or mechanisms cannot necessarily be inferred.…”
Section: Mutational Modes Of Resistancementioning
confidence: 90%
See 3 more Smart Citations
“…102 Interestingly, in both K. pneumoniae and A. baumannii, genomic sequencing studies have found mutations in a common regulatory pathway controlling LPS modification systems, indicating that LPS modification is key to resistance in both species. [103][104][105] This genomederived hypothesis that altered LPS modification underlies resistance was ultimately confirmed for both organisms by comparing LPS modifications in susceptible and resistant isolates. 103,106 An important caveat in studying resistance evolution in individual patients is that the larger epidemiological significance of observed resistance mutations or mechanisms cannot necessarily be inferred.…”
Section: Mutational Modes Of Resistancementioning
confidence: 90%
“…[103][104][105] This genomederived hypothesis that altered LPS modification underlies resistance was ultimately confirmed for both organisms by comparing LPS modifications in susceptible and resistant isolates. 103,106 An important caveat in studying resistance evolution in individual patients is that the larger epidemiological significance of observed resistance mutations or mechanisms cannot necessarily be inferred. This disconnect between short-term and long-term impacts of resistance evolution is due to fitness costs associated with resistance that might limit the ultimate viability of resistant mutants once the selective pressure of the drug is removed.…”
Section: Mutational Modes Of Resistancementioning
confidence: 90%
See 2 more Smart Citations
“…The colistin-resistant K. pneumoniae strains have altered LPS structures that limit the binding of the drug to the bacterial membrane [97]. Recent characterization of LPS from infected patients showed the rapid acquisition of genomic- and plasmid-mediated mutations, leading to alterations in the composition of lipid A and colistin resistance [98]. Perhaps the most concerning of these genetic elements is the emergence of the mobilized colistin resistance ( mcr-1 ), a mobile plasmid rapidly shared amongst all members of the Enterobacteriaceae [99].…”
Section: Surface Properties Of K Pneumoniae and Immune Recognitionmentioning
confidence: 99%